Designing an Integrated Systematic Excavator for Agricultural Land - Al-Jaaf, Jassim M.; Mohammad, Kareem K.; Mahmood, Najmuldeen Y. (Nahrain University College of Engineering Journal, 2010)
In this research a complete design of a plough for agricultural land has been achieved. This is a heoretical study, design and invention, for it is considered like the ones available now. Precisely, it is a borne type which can be carried on a vehicle. The optimal design has been reached through making some primary designs for the research on well excavated land by using spiral digging blades which unearths the earth on both sides. These blades are fixed on a subjacent system raised by a hydraulic tool when the digging process finishes. This hydraulic tool enables to obtain a digging successive course by controlling the process of lowering the lower system gradually to perform the digging process by a control system connected to the hydraulic tool. Throughout observation of the previous researches related to plowing [2, 3], it has been found that loads are put on the most digging blades of the ploughs to increase the digging efficiency and to reach deeper points. This has been taken into account in our presented research by designing springs between the lower system mentioned above and the upper fixed system. From this we get a downward force which will be observed by detailed drawings. Besides, hindering digging blades by solid materials in the earth has been given attention for they penetrate the earth to a depth of (30 cm) by our designing the springs to raise the lower system when hindered and later to reach a system design as a whole